Induced sputum as a method for detection of systemic sclerosis-related interstitial lung disease - ÇELİKEL, ÇİĞDEM; KARAKURT, SAİT (SPRINGER HEIDELBERG, 2012)
Inducted sputum (IS) is a non-invasive procedure that can be used for collection of airway secretions. The aim of our study is to evaluate the clinical usefulness of IS for detection of airway inflammation in systemic sclerosis (SSc). Bronchoalveolar lavage and IS were performed to 20 patients with SSc. Eighteen patients who were referred to pulmonary medicine for bronchoalveolar lavage due to other reasons were also recruited for cell counts comparisons. Spirometry, echocardiography and thorax CT (HRCT) imaging were also performed to all patients. Mean macrophage and lymphocyte counts were found to be increased in IS of SSc patients compared with that of control (58.4 +/- A 14.5% vs. 31.3 +/- A 16.3%, 30.2 +/- A 15.4% vs. 15.0 +/- A 11.5% P < 0.001), whereas mean neutrophil count was lower in the SSc patients (4.1 +/- A 4.5% vs. 17.2 +/- A 13.1%, P < 0.05). Significant correlations were noted between BAL and IS findings for macrophage (r = 0.55, P = 0.02) lymphocyte (r = 0.65, P < 0.01) and total cell counts (r = 0.45, P = 0.06). IS is an easy and reliable method for the detection of alveolitis and can be used for early detection of lung involvement in scleroderma.
Keywords: Scleroderma; Induced sputum; Interstitial lung disease; BRONCHOALVEOLAR LAVAGE; SARCOIDOSIS; MANAGEMENT; INDUCTION